Properties of an alkali-thermo stable xylanase from Geobacillus thermodenitrificans A333 and applicability in xylooligosaccharides generation - Marcolongo, L. (2016)
An extracellular thermo-alkali-stable and cellulase-free xylanase from Geobacillus thermodenitrificans A333 was purified to homogeneity by ion exchange and size exclusion chromatography. Its molecular mass was 44 kDa as estimated in native and denaturing conditions by gel filtration and SDS-PAGE analysis, respectively. The xylanase (GtXyn) exhibited maximum activity at 70 °C and pH 7.5. It was stable over broad ranges of temperature and pH retaining 88 % of activity at 60 °C and up to 97 % in the pH range 7.5–10.0 after 24 h. Moreover, the enzyme was active up to 3.0 M sodium chloride concentration, exhibiting at that value 70 % residual activity after 1 h. The presence of other metal ions did not affect the activity with the sole exceptions of K+ that showed a stimulating effect, and Fe2+, Co2+ and Hg2+, which inhibited the enzyme. The xylanase was activated by non-ionic surfactants and was stable in organic solvents remaining fully active over 24 h of incubation in 40 % ethanol at 25 °C. Furthermore, the enzyme was resistant to most of the neutral and alkaline proteases tested. The enzyme was active only on xylan, showing no marked preference towards xylans from different origins. The hydrolysis of beechwood xylan and agriculture-based biomass materials yielded xylooligosaccharides with a polymerization degree ranging from 2 to 6 units and xylobiose and xylotriose as main products. These properties indicate G. thermodenitrificans A333 xylanase as a promising candidate for several biotechnological applications, such as xylooligosaccharides preparation.